Oil quality characterization of the Arauco variety from the main olive growing areas of Mendoza (Argentina) - Banco, Adriana Pamela; Puertas, Carlos Marcelo; Trentacoste, Eduardo Rafael; Monasterio, Romina Paula (Instituto de la Grasa, CSIC, 2022)
‘Arauco’ forms part of the over two thousand olives (Olea europaea L.) varieties identified worldwide with the peculiarity of being the only recognized variety from Argentina. In this work, the fruit and oil characteristics from the ‘Arauco’ variety cultivated in the three main olive growing zones of Mendoza province (Argentina) were evaluated over two harvests (2016 and 2017). The characteristics assessed were oil and water concentrations, pulp/pit ratio, industrial yield, oxidative stability, fatty acid profile, total phenols and total flavonoids, among others. The results showed relatively high oleic acid and phenolic contents, together with low acidity and extinction coefficients (K232 and K270), as well as a well-balanced fatty acid profile. In addition, three interesting relationships among oxidative stability and ratios of monounsaturated fatty acids/polyunsaturated fatty acids (R2=0.96), oleic/linoleic (R2=0.96) and stearic acid (R2=0.93) were observed. These results showed that the ‘Arauco’ variety cultivated in Mendoza provides excellent oil quality.